Acute Effect of Dynamic and Static Stretching Exercises on Targeting Performance in Archery - Turna, Bulent; Bayazit, Burcu; Eryucel, Mehmet Emre; Yildiz, Mustafa; Karademir, Mehmet Bilgin (Progress in Nutrition, 2021)
Study Objectives: This study aimed to investigate the acute effects of dynamic and static stretching exercises on targeting performance in archery. Methods: Thirty intermediate archers participated in the study, 15 females and 15 males. Participants were assigned into three groups randomly which are no stretching (NS), static stretching (SS), and dynamic stretching (DS). 3*10 Arrow shooting test (18 m) were applied to each group on three different days (with minimum 72-hour resting intervals between days) after each different stretching protocols with a random order. SPSS 20 statistical package program was used for statistical analyses and the significance level was set at p <0.05. Friedman test was used to compare different stretching protocols, and Wilcoxon Signed Rank Tests were used to determine the differences between the groups. A statistically significant difference was found between the groups in the comparison of an arrow shot tests performed after different stretching protocols (p <0.05). Results: As a result of the paired comparisons, there was no statistically significant difference between SG and GY groups (p> 0.05), but a statistically significant difference was found between SG and DG groups and GY and DG groups (p <0.05). Conclusion: It was found that static stretching exercises performed after submaximal running and Archery specific warm-up did not affect targeting performance, but dynamic stretching exercises affected performance negatively.